Multiplier Effect Analysis of Tourism Sector In The West Java Province (Efficient: Indonesian Journal of Development Economics, 2025)
The tourism sector in West Java Province has significant potential, with increasing tourist visits. However, its economic impact remains suboptimal. This study examines forward and backward linkages, multiplier effects, and the impact of sectoral shocks using input-output analysis with secondary data from BPS. Results indicate that the tourism sector ranks third in forward linkage, led by the transportation and warehousing sub-sector, and fourth in backward linkage, also dominated by transportation and warehousing. In terms of multiplier effects, the tourism sector achieves the third-highest output effect for both type I and type II, though its income and workforce multiplier values remain below average, limiting contributions to income growth and job creation. Shock impact analysis reveals that investment in the tourism sector could enhance output, income, and employment, highlighting its potential as a driver of regional economic growth when appropriately supported.